Large-scale self-assembled nanophotonic scintillators for X-ray imaging - Louis Martin-Monier; Simo Pajovic; Muluneh G. Abebe; Joshua Chen; Sachin Vaidya; Seokhwan Min; Seou Choi; Steven E. Kooi; Bjorn Maes; Juejun Hu; Marin Soljačić; Charles Roques-Carmes (Nature Communications)
Abstract Scintillators convert X-ray energy into visible light and are critical for imaging technologies. Their widespread use relies on scalable, high-quality manufacturing methods. Nanophotonic scintillators, featuring wavelength-scale nanostructures, can offer improved emission properties such as higher light yield, shorter decay times, and enhanced directionality. However, achieving scalable fabrication of these structures remains challenging. Here, we present a scalable fabrication method for large-area nanophotonic scintillators based on the self-assembly of chalcogenide glass photonic crystals. This technique enables the production of nanophotonic scintillators over wafer-scale areas, achieving a six-fold enhancement in light yield compared to unpatterned scintillators. By studying surface nanofabrication disorder, we show its impact on imaging performance and provide a route towards scintillation enhancements without compromising resolution. We demonstrate the practical applicability of our nanophotonic scintillators through X-ray imaging of biological and inorganic specimens. Our results could enable the industrial implementation of a new generation of nanophotonic-enhanced scintillators.